A biological assessment of the Cape knifejaw (Oplegnathus conwayi) an endemic South African teleost - Foster, Ryan Matthew (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The South African spearfishery forms a small component of South Africa's complex coastal fishery. Although the smallest, this fishery sector has the largest proportion of data deficient species, and as a consequence is poorly managed. Oplegnathus conwayi (Cape knifejaw) is an example of one of these species for which there is very little and outdated biological and ecological data. This species is among the top target species by recreational spearfishers in South Africa. This thesis aimed to improve our socio-ecological knowledge of the South African spearfishery through the collection of biological and Fishers' Ecological Knowledge (FEK) information on Oplegnathus conwayi, and human dimension information on the South African spearfishery. Monthly biological samples were collected through routine sampling (spearfishing) and augmented by recreational spearfishers. A total of 254 fish were collected from the warm-temperate coastal zone (East London "“ Cape Agulhas), 28 from the sub-tropical zone (Durban "“ East London) and 23 from the cool-temperate zone (Cape Agulhas "“ Cape Point). The results indicated that Oplegnathus conwayi is a slow-growing species, with a maximum recorded age of 27 years. The population sex ratio was skewed, with males dominant in the population (1M:0.6F). The length- and age-frequency distributions were, however, similar for both sexes. No significant differences were observed between male and female growth (LRT, p > 0.05), with the overall population growth curve being best described as L(t) = 697.15(1-e-0.06(t-6.30)). Males matured at a slightly larger size than females, however, no significant differences were observed (LRT, p > 0.05). The length- and age- at-50% maturity was 330 mm (FL) and 5.73 years for the full population, respectively. Histological analyses showed that Oplegnathus conwayi are asynchronous spawners with a gonochoristic reproductive style. Macroscopic staging and gonadosomatic index results indicated a protracted spawning season for Oplegnathus conwayi, with a peak in spring. A survey was designed and disseminated to collect FEK on the biology and population status of Oplegnathus conwayi and human dimension information on South Africa's spearfishery. A total of 103 survey responses were received, of which 94 were regarded as specialised (spearfishers who had greater experience, skill and avidity, and maintained spearfishing as an important component of their lifestyle) spearfishers. Based on the responses of the specialist spearfishers, the top four main species caught by spearfishers from this survey were Seriola lalandi (13.9%), Pachymetopon grande (11.7%), Oplegnathus conwayi (11.4%) and Sparodon durbanensis (11%), and the majority of respondents indicated that there had been no changes in abundance, size and catches of these species in the years that they had been spearfishing. Respondents indicated that Oplegnathus conwayi are most commonly targeted in the Eastern Cape and are found at depths of up to 40 m. Respondents also indicated that there may be a seasonal onshore (Summer/Winter) and offshore (Summer/Winter) migration with year-round spawning and a peak in November, December and January. The incorporation of spearfishers into the data collection, both through the collection of specimens and their FEK, was beneficial to this study. Besides providing samples from a broader geographical range than the primary collection area, the collaboration with spearfishers has promoted the inclusion of this group into the management system. The findings of this study also suggest that FEK data can be more reliable if the concept of recreational specialisation is incorporated into data collection. While the FEK suggested that the population was stable, a stock assessment is necessary to fully understand the population status and implement management strategies. Nevertheless, the key life history characteristics (slow growth and late maturation) observed in this study are characteristic of species that is vulnerable to overexploitation, and thus the precautionary approach should be applied. The reproductive information collected in this study has provided information for the implementation of an appropriate size limit regulation for Oplegnathus conwayi. Here, a minimum size limit of 400 mm TL, which corresponds approximately with the length-at-50% maturity of 330 mm FL, would be appropriate to allow fish to mature and spawn, and reduce the likelihood of recruitment overfishing. Reduction in the bag limit from five to two fish per person per day may also be appropriate as a precautionary measure until a stock assessment has been completed. Finally, the incorporation of stakeholder into biological collection and the use of FEK may be a useful approach for other data deficient species and in countries with limited resources for ecological research.
Keywords: Perciformes -- South Africa; Osteichthyes -- South Africa; Fisheries -- South Africa; Perciformes Growth; Perciformes Age; Perciformes Reproduction; Sampling Citizen participation; Cape knifejaw (Oplegnathus conwayi)